Pathways to Resilience in Women Experiencing Financial Disempowerment - Fernandes, Lucas (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the multidimensional pathways through which women experiencing financial disempowerment construct and enact psychological resilience within the socio-cultural context of Spain. Methods and Materials: Using a qualitative exploratory design, in-depth semi-structured interviews were conducted with 16 women aged 26 to 52 who self-identified as financially disempowered. Participants were recruited from urban and semi-urban areas in Spain through community organizations and support networks. Data collection continued until theoretical saturation was achieved. Interviews, lasting between 50 to 75 minutes, were audio-recorded, transcribed verbatim, and analyzed using thematic analysis with NVivo 14 software. Open, axial, and selective coding procedures were applied to identify core themes related to internal coping, social support, and structural adaptation. Findings: Three overarching themes emerged: (1) Internal Coping Mechanisms—including emotional regulation, cognitive reframing, goal setting, and spiritual anchoring; (2) Social Support and Relationships—encompassing peer support, family dynamics, mentorship, and digital community engagement; and (3) Structural Navigation and Empowerment—involving financial literacy, employment strategies, institutional navigation, and gender-based advocacy. Participants emphasized that resilience was not an innate trait but a dynamic, contextually driven process shaped by both personal agency and access to relational and institutional resources. Quotations revealed resilience as a negotiated response to chronic instability rather than a fixed psychological quality. Conclusion: The study underscores the multifaceted nature of resilience among financially disempowered women, revealing how they integrate personal strategies, relational resources, and structural engagement to cope with adversity.